Neutrophil extracellular Taps play an important role in clearance of Streptococcus suis in vivo. (15th April 2016) - Zhao, Jianqing; Lin, Lan; Fu, Lei; Han, Li; Zhang, Anding
ABSTRACT: Streptococcus suis infection induces formation of neutrophil extracellular traps (NETs) in vitro ; however, the contribution of NETs‐mediated killing to the pathogenesis of S. suis in vivo is yet to be elicited. The findings of the present study indicated that extracellular DNA fiber can be induced in a murine model in response to S. suis infection. A nuclease that destroys their structure was used to evaluate the role of NETs on S. suis infection. Treatment with nuclease resulted in a greater bacteria load and higher serum TNF‐α concentrations in response to S. suis infection, indicating that NETs structure played an essential role in S. suis clearance and inflammation. Furthermore, nuclease treatment resulted in more severe clinical signs during and higher mortality from S. suis infection. These findings indicated that NETs structure contributes to protection against S. suis infection.